2015
DOI: 10.1016/j.phpro.2015.08.155
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Phononic Crystal Constituted of Piezoelectric Layers Using Electrical Impedance Measurement

Abstract: Active materials are investigated as a tuning possibility for phononic crystals. Electromechanical properties of piezoelectric materials electrical and mechanical variables are coupled. Thus, the propagation properties of elastic waves can be tuned using electrical impedance load connected to the piezoelectric layer. In this study, a theoretical one-dimensional model is proposed to calculate the electrical impedance of an active layer located inside a finite periodic structure including both piezoelectric and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The dispersion curves of a (Piezo/passive) PPC have been calculated according to equation (13). Those results have been compared and validated on the basis of the (Pz26/PMMA) PPC configuration depicted in the work of S.A. Mansoura et al [17], in the case of short-circuit load (Z a = 0), and an open-circuit load (Z a = +∞). Following this validation stage, as illustrated in Figure 5, the dispersion curves of (Pz26/PMMA) PPC are studied according to the dynamic resistance of the diode R D connected to the electrodes of the Pz26 plate.…”
Section: Accepted Manuscript 41 Dispersion Curves Of (Pz26/pmma) Ppcmentioning
confidence: 99%
See 1 more Smart Citation
“…The dispersion curves of a (Piezo/passive) PPC have been calculated according to equation (13). Those results have been compared and validated on the basis of the (Pz26/PMMA) PPC configuration depicted in the work of S.A. Mansoura et al [17], in the case of short-circuit load (Z a = 0), and an open-circuit load (Z a = +∞). Following this validation stage, as illustrated in Figure 5, the dispersion curves of (Pz26/PMMA) PPC are studied according to the dynamic resistance of the diode R D connected to the electrodes of the Pz26 plate.…”
Section: Accepted Manuscript 41 Dispersion Curves Of (Pz26/pmma) Ppcmentioning
confidence: 99%
“…They have shown that it is possible to considerably modulate the properties of a PC made up of alternating piezoelectric and elastic layers by modifying the electrical boundary conditions of active inclusions. The case of the connexion of an electrical passive load across the piezoelectric element has been investigated, with an electrical open-circuit or short-circuit by Mansoura et al [16,17] in the case of bulk waves and by C. Vasseur et al [18] in the case of guided waves, and with resistive loads by Airoldi et al [19]. Frequency dependant electrical load have also been investigated with a capacitance by Degraeve et al [20][21][22] and Ponge et al [23,24], with an inductance by Mansoura et al [25], and with a resonant parallel LC load by E.A.…”
Section: Introductionmentioning
confidence: 99%
“…The influences of the electrical potential and the incident angle on these wave properties were also investigated. As for the pure longitudinal waves and vibrations along the thickness in finite thickness plates have bounding plane parallel to the layering plane: Mansoura et al [66,67] theoretically and experimentally investigated the electrical impedance of one piezoelectric layer within phononic crystals made of alternating piezoelectric and elastic layers while the other piezoelectric layers were connected to the external circuit including electric-open, electric-short, and external capacitance conditions, which is related to the band structures and transmissions together with the electromechanical coupling. Mansoura et al [68] further verified, by comparing the experimentally measured transmissions with theoretically analyzed dispersion curves, the wave control in phononic piezoelectric elastic crystals through the negative capacitance connected on the electroded faces of piezoelectric layers that broadening band gaps.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the above-mentioned three introduced materials, another smart material, which is the fourth introduced material, is the piezoelectric material, which is also dependent on electric fields like the dielectric elastomer, which has been extensively used in periodically laminated structures, i.e., one-dimensional (1D) piezoelectric layered phononic crystals. Because the electrical field is relatively easy to control and the piezoelectric effect is linear coupling between the electrical and mechanical fields, the elastic wave propagation and its tuning by the electrical conditions in periodically laminated piezoelectric composites have received extensive attention during the last two decades [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. The earlier literatures on this topic only considered the relatively simple electrical boundaries, i.e., the electric-open and electric-short conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These introduced tunable components contain electrical impedance, capacitance, voltage, and inductance. By adopting the electrical impedance condition, Mansoura et al [40,41] investigated theoretically and experimentally the bandgap control of elastic waves perpendicular to the layers and found that the change of electric impedance can be used to obviously modify the band structure and acoustic transmission. When considering the applied capacitance, Mansoura et al [42] also proposed the use of negative capacitance values to achieve unusual band properties.…”
Section: Introductionmentioning
confidence: 99%